The RIghts of the DIsabled and InteractIon between the European UnIon Law and European ConventIon on Human RIghts System - (:unkn) unknown (My University, 2018)
The rights of the disabled is an importantpart of human rights law. In this framework,the European Union (EU) Law focuses onthe issue and there are judgments from theCourt of Justice of the European Union (CJEU)to analyse. The United Nations Conventionon the Rights of Persons with Disabilities(UNCRPD) is the central legal instrument totake into consideration with regard to therights of the disabled especially in terms ofthe EU being party to the Convention.In parallel, although there are no specificprovisions in the European Convention onHuman Rights (ECHR) and protocols on therights of the disabled, there are judgmentsof the European Court of Human Rights(ECtHR) to concentrate upon. Since, it isalso necessary to make an emphasis on theinteraction between the EU Law and ECHRsystem by specific references of EU Law, thestudy concentrates mainly upon this aspect.At the end of the study, the importanceof the protection of the rights of the disabledis determined. The EU, as a legal entity, beingparty to the UNCRPD together with theECtHR addresing the issue in many judgmentsare only two justifications for this factualconclusion. Since the UNCRPD is centralfor the protection of rights of the disabled,a specific court to address interdisciplinaraspects of disability is suggested in thisrespect.

Engelli hakları, insan hakları hukukunun önemli bir parçasıdır. Bu çerçevede, Avrupa Birliği (AB) konu üzerine odaklanmakta ve Avrupa Birliği Adalet Divanı (ABAD)’nın konu hakkında analiz edilmesi gereken kararları bulunmaktadır. Birleşmiş Milletler Engellilerin Haklarına İlişkin Sözleşme (BMEHS), özellikle AB’nin taraf olmasıyla, engelli hakları açısından ele alınması merkezi hukuki kaynak niteliğini taşımaktadır. Paralel olarak, Avrupa İnsan Hakları Sözleşmesi (AİHS) ve protokollerinde engelli hakları ile ilgili özel hükümler bulunmasa da, ele alınması gereken Avrupa İnsan Hakları Mahkemesi kararları bulunmaktadır. Ayrıca, AB Hukuku’ndaki spesifik atıflar sebebiyle de, AB Hukuku ile Avrupa İnsan Hakları Sözleşmesi sistemi arasındaki etkileşime vurgu yapılması gerekli olduğundan, çalışma temel olarak bu boyut ile ilgilenmektedir. Çalışmanın sonunda, engelli haklarının korunmasının önemi tespit edilmektedir. AB’nin, bir tüzel kişilik olarak BMEHS’ne taraf olması ve AİHM’nin birçok kararında konuyu ele alması, bu gerçek sonucun sadece iki gerekçesidir. BMEHS engellilerin haklarının korunması için merkezi olduğundan, engelliliğin disiplinlerarası yönlerini ele alan özel bir mahkemenin kurulması bu anlamda önerilmektedir.
Engelli Hakları ve Avrupa Birliği Hukuku ile Avrupa İnsan Hakları Sözleşmesi Sistemi Arasındaki Etkileşim
Keywords: Hukuk